Findable Accessible Interoperable Re-usable (FAIR) diffraction data are coming to protein crystallography - Helliwell, John R; Minor, Wladek; Weiss, Manfred S; Garman, Elspeth F; Read, Randy J; Newman, Janet; van Raaij, Mark J; Hajdu, Janos; Baker, Edward N (IUCrJ, 2019)
The policy of IUCr Journals on diffraction data is defined.
Keywords: diffraction data; FAIR; IUCr policy